Effect of thyme/cumin essential oils and butylated hydroxyl anisole/butylated hydroxyl toluene on physicochemical properties and oxidative/microbial stability of chicken patties - Saricoban, Cemalettin; Yilmaz, Mustafa Tahsin (OXFORD UNIV PRESS, 2014)
In this study, effects of thyme/cumin essential oils (EO) and butylated hydroxyl anisole (BHA)/butylated hydroxyl toluene (BHT) on physicochemical properties and storage stability of chicken patties were compared in different storage periods (0, 3, 7, 14, 21, and 28 d). It was found that there were significant (P < 0.05) differences between physicochemical properties of patty samples treated with EO and the synthetic antioxidants. The EO showed similar performance to those of BHA and BHT in limiting TBARS values of chicken patty samples. Similarity in performance was also the case for microbial stability (total aerobic mesophilic, psychrotrophic, lactic acid, and coliform bacteria as well as molds and yeasts); namely, their effects were significant (P < 0.05). Effect of thyme EO was significant (P < 0.05) and remarkable, not allowing any coliform bacteria to grow in the samples. Given that EO were obtained from natural sources, the data suggested that the EO might be more useful than their synthetic counterparts, BHA and BHT, as additives for chicken patties to maintain oxidative/microbial stability and increase shelf life.
Keywords: chicken patty; thyme/cumin essential oil; butylated hydroxyl anisole/butylated hydroxyl toluene; oxidative stability; microbial stability; COLOR; ANTIOXIDANT; PORK; MEAT; HYDROXYANISOLE; DENATURATION; COMPONENTS; OXIDATION; POULTRY; FOOD; Agriculture